Porcine Primordial Germ Cell-Like Cells Generated from Induced Pluripotent Stem Cells Under Different Culture Conditions - Pieri, Naira Caroline Godoy; de Souza, Aline Fernanda; Botigelli, Ramon Cesar [UNESP]; Pessôa, Laís Vicari de Figueiredo; Recchia, Kaiana; Machado, Lucas Simões; Glória, Mayra Hirakawa; de Castro, Raquel Vasconcelos Guimarães [UNESP]; Leal, Diego Feitosa; Fantinato Neto, Paulo; Martins, Simone Maria Massami Kitamura; dos Santos Martins, Daniele; et al. (Springer Nature, 2021)
Culture conditions regulate the process of pluripotency acquisition and self-renewal. This study aimed to analyse the influence of the in vitro environment on the induction of porcine induced pluripotent stem cell (piPSCs) differentiation into primordial germ cell-like cells (pPGCLCs). piPSC culture with different supplementation strategies (LIF, bFGF, or LIF plus bFGF) promoted heterogeneous phenotypic profiles. Continuous bFGF supplementation during piPSCs culture was beneficial to support a pluripotent state and the differentiation of piPSCs into pPGCLCs. The pPGCLCs were positive for the gene and protein expression of pluripotent and germinative markers. This study can provide a suitable in vitro model for use in translational studies and to help answer numerous remaining questions about germ cells. Graphical abstract: [Figure not available: see fulltext.]
Keywords: PGCs; Porcine; Regenerative medicine; Reproduction; Translational medicine